2017
DOI: 10.18632/oncotarget.18760
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal radiation dose for non-operable esophageal cancer? Dissecting the evidence in a meta-analysis

Abstract: The standard radiation dose 50.4 Gy with concurrent chemotherapy for localized inoperable esophageal cancer as supported by INT-0123 trail is now being challenged since a radiation dose above 50 Gy has been successfully administered with an observable dose–response relationship and insignificant untoward effects. Therefore, to ascertain the treatment benefits of different radiation doses, we performed a meta-analysis with 18 relative publications. According to our findings, a dose between 50 and 70 Gy appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…The different results between the two subgroup analyses can be partially explained by the theory that 45 to 50-Gy radiation dose can be used to control microscopic tumors of SCC or AC, and at least 60 Gy is required aiming to control gross tumor ( 29 31 ). Our analysis is also in accordance with some nearly published studies ( 26 , 32 ). The results suggest that when the dose of radiotherapy is raised within a certain range below the 60 Gy dose threshold, it would not improve the OS and local–regional control of esophageal carcinoma patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The different results between the two subgroup analyses can be partially explained by the theory that 45 to 50-Gy radiation dose can be used to control microscopic tumors of SCC or AC, and at least 60 Gy is required aiming to control gross tumor ( 29 31 ). Our analysis is also in accordance with some nearly published studies ( 26 , 32 ). The results suggest that when the dose of radiotherapy is raised within a certain range below the 60 Gy dose threshold, it would not improve the OS and local–regional control of esophageal carcinoma patients.…”
Section: Discussionsupporting
confidence: 93%
“…For patients with esophageal cancer receiving CCRT, the recommended radiation dose remains controversial. Although several meta-analyses were published regarding the optimal radiotherapy dose of CCRT for esophageal carcinoma ( 26 28 ), the robustness of their findings was inadequate due to the limited sample size. Moreover, some outdated radiation techniques, including the improper multiple field technique, cobalt-60 equipment, and 2D-CRT, were included in these studies, introducing more heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, we defined a radiation dose of > = 60 Gy as HD-RT and < 60 Gy as SD-RT. Furthermore, only those studies using 60Gy as a threshold value for high dose and standard dose were included in our meta-analysis, and we have found that high radiation dose of > = 60 Gy was associated with better OS, PFS and LRFS, which is consistent with Chen’s study and Song’s study [8, 21]. However, how high radiation dose is appropriate for ESCC patients?…”
Section: Discussionsupporting
confidence: 83%
“…However, this review was a compilation of single treatment arm, with only 3 included studies containing both a HD-RT (≥ 60 Gy) arm and SD-RT arm. Another meta-analysis has indicated that patients who received ≥60 Gy radiation had a significantly better prognosis as compared with < 60 Gy [21]. The studies including patients received < 50 Gy radiation and the studies including patients diagnosed as esophageal adenocarcinoma were included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analyses by Song et al in 2015 included 55 articles and concluded that high-dose radiation increased treatment response and 5-year OS rates while decreasing LRF and distant failure rates with without additional toxicity, notably for ESCC patients [31] . Another study by Chen et al analyzed 18 articles and also found that a dose of ≥ 60 Gy appeared to improve OS and LRC, notably in Asian patients [32] . Luo et al reached a similar conclusion [33] .…”
Section: Discussionmentioning
confidence: 98%